A review of the surgical conversion rate and independent management of spinal extended scope practitioners in a secondary care setting - Wood, Lianne; Hendrick, Paul; Boszczyk, Bronek; Dunstan, Eleanor (Royal College of Surgeons of England, 2016)
INTRODUCTION Spinal orthopaedic triage aims to reduce unnecessary referrals to surgical consultants, thereby reducing waiting times to be seen by a surgeon and to surgical intervention. This paper presents an evaluation of a spinal orthopaedic triage service in the third largest spinal unit in the UK. METHODS A retrospective service evaluation spanning 2012 to 2014 was undertaken by members of the extended scope practitioner (ESP) team to evaluate the ESPs’ ability to manage patient care independently and triage surgical referrals appropriately. Data collected included rates of independent management, referral rates for surgical consideration and conversion to surgery. Patient satisfaction rates were evaluated retrospectively from questionnaires given to 5% of discharged patients. RESULTS A total of 2,651 patients were seen. The vast majority (92%) of all referrals seen by ESPs were managed independently. Only 8% required either a discussion with a surgeon to confirm management or for surgical review. Of the latter, 81% were considered to be suitable surgical referrals. A 99% satisfaction rate was reported by discharged patients. CONCLUSIONS ESP services in a specialist spinal service are effective in managing spinal conditions conservatively and identifying surgical candidates appropriately. Further research is needed to confirm ESPs’ diagnostic accuracy, patient outcomes and cost effectiveness.